2018
DOI: 10.1097/brs.0000000000002387
|View full text |Cite|
|
Sign up to set email alerts
|

Hyperbaric Oxygen Therapy After Acute Thoracic Spinal Cord Injury

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…As the urethra of female rats is shorter compared with that of male rats, urination recovery and abdominal massage may be easier following SCI in female rats. Therefore, female rats were selected as an animal model of spinal cord injury to minimize the experimental error caused by urinary dysfunction that occurred when not using female rats alone, as observed in previous studies ( 47 , 64 , 65 ). In the early stage of spinal cord injury (1 week) in the present study, the rats received abdominal massages every 6 h to assist with emptying their bladders until independent urination was possible.…”
Section: Discussionmentioning
confidence: 99%
“…As the urethra of female rats is shorter compared with that of male rats, urination recovery and abdominal massage may be easier following SCI in female rats. Therefore, female rats were selected as an animal model of spinal cord injury to minimize the experimental error caused by urinary dysfunction that occurred when not using female rats alone, as observed in previous studies ( 47 , 64 , 65 ). In the early stage of spinal cord injury (1 week) in the present study, the rats received abdominal massages every 6 h to assist with emptying their bladders until independent urination was possible.…”
Section: Discussionmentioning
confidence: 99%
“…Studied indicated that HBOP has positive effects on traumatic brain injury, ischemic stroke, and spinal cord injury . Recently, there is also discovered that HBOP provides neuroprotective effect on ICH .…”
Section: Discussionmentioning
confidence: 99%
“…Studied indicated that HBOP has positive effects on traumatic brain injury, 1,20 ischemic stroke, 21,22 and spinal cord injury. 2,3 Recently, there is also discovered that HBOP provides neuroprotective effect on ICH. 6,7 HBOP-induced activation of ribosomal protein S6 kinases (p70 S6 K), an important enzyme in protein synthesis, causes HO-1 upregulation and reduces brain edema.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations